1999
DOI: 10.1006/cbir.1999.0424
|View full text |Cite
|
Sign up to set email alerts
|

REACTIVE OXYGEN SPECIES INDUCE APOPTOSIS OF SYNOVIOCYTES IN VITRO. α‐TOCOPHEROL PROVIDES NO PROTECTION

Abstract: Reactive oxygen species (ROS) are released during the inflammation of the synovial membrane associated with cartilage degradation in osteoarthritis. In this work, we exposed synoviocytes to superoxide anions at concentrations that may cause either apoptosis or necrosis. We studied membrane organization, dehydrogenase mitochondrial activity and nuclear morphology and integrity, to determine the nature of the death process initiated by superoxide anions and tried to counteract ROS effects with alpha-tocopherol. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 14 publications
0
14
0
1
Order By: Relevance
“…Many studies focused on damaging effects of oxidative and nitrosative agents, 911 whereas in the following the differential role of Radical oxygen species (ROS) and radical nitric species (RNS) in osteoarthritis came into focus. A study comparing the effects of nitric oxide and oxidative dysbalance in OA and rheumatoid arthritis postulated a major role of nitric oxide (NO) to modulate chondrocyte function in OA.…”
Section: Lessons From Actual Studiesmentioning
confidence: 99%
“…Many studies focused on damaging effects of oxidative and nitrosative agents, 911 whereas in the following the differential role of Radical oxygen species (ROS) and radical nitric species (RNS) in osteoarthritis came into focus. A study comparing the effects of nitric oxide and oxidative dysbalance in OA and rheumatoid arthritis postulated a major role of nitric oxide (NO) to modulate chondrocyte function in OA.…”
Section: Lessons From Actual Studiesmentioning
confidence: 99%
“…It may therefore be inferred that decreased intracellular riboflavin on day 3 in vitamin E cells may be due to increased lipid peroxidation affecting the membranes and causing excretion of riboflavin extracellularly. It is suggested that even at a concentration of 1 mM vitamin E does not prevent membrane damage, but rather would produce alkoxyl radicals than scavenge peroxyl radicals [27]. Vitamin E can act as a prooxidant rather than an antioxidant when co-oxidants such as vitamin C are not available to neutralize the tocopherol radical when oxidative stress is mild [28].…”
Section: Influence Of Vitamin E On Antioxidant Enzymes Gsh and Lipidmentioning
confidence: 99%
“…Lorsqu'ils sont activés, les neutrophiles roulent, puis adhèrent et infiltrent rapidement le site lésé ( Figure 2C, Figure 4A) pour libérer ensuite un arsenal de molécules pro-inflammatoires, parmi lesquelles des chimiokines, des radicaux libres et des protéinases. La libération de radicaux libres de l'oxygène et de l'azote, durant cette phase catabolique, peut entraîner des dommages cellulaires [1], ainsi que l'apoptose des cellules propres au tissu lésé ( Figure 2D) [2]. Il est donc probable que le stress oxydatif puisse provoquer l'apoptose des ténocytes (fibroblastes tendineux) [3] et interférer ainsi avec le processus de réparation du tendon.…”
Section: Blessure Et Réaction Inflammatoireunclassified